2017
DOI: 10.2503/hortj.okd-027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO<sub>2</sub> Enrichment on Growth and Flowering of <i>Phalaenopsis</i>

Abstract: To increase the photosynthesis of crop and improve plant quality, we evaluated the effect of elevated CO 2 on vegetative growth and flowering in Phalaenopsis 'Fuller's Pink Swallow'. Plants were exposed to 450 (control), 800, 1600, and 2400 μmol·mol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Flower spike length of Phalaenopsis Taisuco Kochdian increased with increasing K concentration to 400 mg•L -1 K, regardless of the medium (Wang, 2007). Flower spike length decreased with elevated atmospheric CO 2 concentrations of 800 -1,600 µmol•mol -1 ; however, it increased under 2,400 µmol•mol -1 CO 2 compared to those under ambient CO 2 level in Phalaenopsis 'Fuller's Pink Swallow' (Kim et al, 2017). Our study also revealed that the flower spike length with the effects of CO 2 treatment or EC was varied in phalaenopsis cultivars.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Flower spike length of Phalaenopsis Taisuco Kochdian increased with increasing K concentration to 400 mg•L -1 K, regardless of the medium (Wang, 2007). Flower spike length decreased with elevated atmospheric CO 2 concentrations of 800 -1,600 µmol•mol -1 ; however, it increased under 2,400 µmol•mol -1 CO 2 compared to those under ambient CO 2 level in Phalaenopsis 'Fuller's Pink Swallow' (Kim et al, 2017). Our study also revealed that the flower spike length with the effects of CO 2 treatment or EC was varied in phalaenopsis cultivars.…”
Section: Discussionmentioning
confidence: 86%
“…In our previous study, phalaenopsis exposed to an elevated CO2 level of 800 µmol•mol -1 had increased biomass production (Kim et al, 2017). Elevated CO 2 levels of either 800 or 1,200 µmol•mol -1 increased flower production in a shortened flowering time in phalaenopsis (Cho et al, 2019).…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, the biomass of some plants, including A. comosus [36], slightly decreased in high CO 2 concentration environments, indicating that there are differences in adaptation between species. Kim et al [37] reported that Phalaenopsis "Fuller's Pink Swallow" did not show a significant difference in shoot biomass and dry weight when CO 2 concentration was increased from 450 to 800 ppm; root dry weight was also not different (1.92 g and 1.96 g, respectively).…”
Section: Growth Characteristicsmentioning
confidence: 98%
“…Fruiting at 100% was only shown in C3, while C1 and C2 showed only 80 and 20%, respectively (Figure 4F). In this regard, Kim et al [35] mention that Phalaenopsis plants exposed to over 800 µmol CO 2 mol −1 before flower spike induction had higher biomass production. However, they also mention flower production and the number of flower buds could be reduced in plants subjected to long CO 2 exposure.…”
Section: Flowering and Fruitingmentioning
confidence: 99%